Everyday problem solving for US court interpreters and the role of research - Melissa Wallace; Aída Martínez-Gómez (Translation and Interpreting : the International Journal of Translation and Interpreting Research, 2023)
This article examines the problem-solving strategies and resources that professional court interpreters in the United States use to address challenges in their daily work, with the goal of investigating the current influence of research on professional practice. The authors report on the first stage of a bipartite study consisting of focus groups conducted in California, New York, and Texas in the spring of 2018, the results of which directly shaped the development of a survey launched at the national level. Participants included a combination of junior and senior interpreters, staff and freelancers, and certified court interpreters with varying degrees of formal interpreter training and education. The anonymized transcripts of these groups were analyzed qualitatively following the principles of thematic analysis and a mixed top-down and bottom-up coding process. The results obtained interrogate the purported divide between theory and practice and reveal valuable information about the areas of professional practice that present challenges for court interpreters, the human and written (scholarly and/or professional) resources that court interpreters use to improve their professional practice and, most germanely, court interpreters’ needs and expectations about scholarly research. Ultimately, the study aims to inform future practice-based research and to improve interpreters’ performance through data-driven suggestions stemming from that research.